Factors to affect inbred beet plants while developing material for linear selection - M. I. Fedorova; E. G. Kozar; S. A. Vetrova; V. A. Zayachkovskyi; V. A. Stepanov (Вавиловский журнал генетики и селекции)
Considering its capacities, the generative system of Beta vulgaris L. is regarded as highly productive. While inbreeding, the reproductive potential of cross-pollinated beet plants with gametophytic self-incompatibility (SI) changes significantly and is determined by a joint effect of multiple factors including the level of inbred depression. In the present study, original data have been obtained revealing relationships between inbred beet seed productivity, its self-incompatibility and microgametophyte parameters, which is crucial for developing and maintaining constant fertile beet lines. It has been discovered that inbred depression increases the number of sterile microgametes and anomalous pollen grains, reduces pollen fertility and the length of pollen tubes. As a result, the seed yield in inbred beet progeny, including SI ones, reduces significantly just after the third inbreeding. At the same time, highly productive inbred beet is characterized by a lower rate of pollen tube growth in vitro. In inbred plants, there is no close relationship between pollen viability and seed productivity, because the elimination of germinated male gametes and degeneration of seed embryos may go over the entire period of fertilization starting its progamic phase. The SI plants have more degenerating embryos than self-fertile ones, but seed vessel outgrowth in the seeds with abortive embryos makes them morphologically similar to fertile seeds. For that reason, when assessing inbred beet plants based on their self-incompatibility/self-fertility, one should consider the qualitative characteristics of the seeds. Using the method of recurrent selection based on such factors as seed productivity, pollen tube length and field germination rate increase the output of plant forms with a potentially high self-compatibility in their progeny. To support such genotypes in the progeny, one has to, starting from the third inbreeding, perform sib crossing to reduce the negative effect of inbred depression and self-incompatibility.